Arithmetic in the adult deaf signing brain. Issue 4 (5th December 2019) - Andin, Josefine; Elwér, Åsa; Mäki‐Torkko, Elina
Abstract: We have previously shown that deaf signers recruit partially different brain regions during simple arithmetic compared to a group of hearing non‐signers, despite similar performance. Specifically, hearing individuals show more widespread activation in brain areas that have been related to the verbal system of numerical processing, i.e., the left angular and inferior frontal gyrus, whereas deaf individuals engaged brain areas that have been related to the quantity system of numerical processing, i.e., the right horizontal intraparietal sulcus. This indicates that compared to hearing non‐signers, deaf signers can successfully make use of processes located in partially different brain areas during simple arithmetic. In this study, which is a conceptual replication and extension of the above‐presented study, the main aim is to understand similarities and differences in neural correlates supporting arithmetic in deaf compared to hearing individuals. The primary objective is to investigate the role of the right horizontal intraparietal gyrus, the left inferior frontal gyrus, the hippocampus, and the left angular gyrus during simple and difficult arithmetic and how these regions are connected to each other. A second objective is to explore what other brain regions support arithmetic in deaf signers. Up to 34 adult deaf signers and the same amount of hearing non‐signers will be enrolled in an functional magnetic resonance imaging study that will include simple and difficult subtraction and multiplication. Brain imaging data will be analyzed using whole‐brain analysis, region of interest analysis and connectivity analysis. This is the first study to investigate neural underpinnings of arithmetic of different difficulties in deaf individuals.